2018
DOI: 10.3892/ol.2018.9519
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR‑204 in pediatric retinoblastoma and its effects on proliferation and apoptosis of cancer cells

Abstract: Expression, clinical significance and molecular mechanism of miR-204 in human retinoblastoma (RB) and para-carcinoma tissues were investigated. A total of 110 cases of RB tissues preserved after ophthalmectomy in the First Affiliated Hospital of Hunan Normal University (People's Hospital of Hunan Province) from April 2013 to June 2017 were collected along with 100 cases of para-carcinoma normal tissues. The expression of miR-204 in RB tissues was detected via reverse transcription-quantitative polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…For example, the expression of miR-204 in Rb patients is dysregulated, and its expression level is related to optic nerve infiltration, lymph node metastasis, and tumour tissue differentiation. miR-204 may affect the proliferation and apoptosis of Rb cells, thereby affecting the development of Rb, which may become an early stage molecular indicator for diagnosing and evaluating the prognosis of Rb (43)(44)(45); miR-338-5p is up-regulated in the serum of patients with Rb, which may play a role in promoting cancer in the occurrence and development of Rb, and has the potential value of the early diagnosis of Rb (46,47). Recent studies have shown that dysregulated miR-592 and miR-217-3p have been reported to be involved in developing many different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression of miR-204 in Rb patients is dysregulated, and its expression level is related to optic nerve infiltration, lymph node metastasis, and tumour tissue differentiation. miR-204 may affect the proliferation and apoptosis of Rb cells, thereby affecting the development of Rb, which may become an early stage molecular indicator for diagnosing and evaluating the prognosis of Rb (43)(44)(45); miR-338-5p is up-regulated in the serum of patients with Rb, which may play a role in promoting cancer in the occurrence and development of Rb, and has the potential value of the early diagnosis of Rb (46,47). Recent studies have shown that dysregulated miR-592 and miR-217-3p have been reported to be involved in developing many different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another group also reported that miR‐211 could modulate cell proliferation through CXCR4 and MAPK signalling (Li, Lv, Wang, & Kuang, ). miR‐204 was reported to inhibit cell proliferation and promote apoptosis through the downregulation of Bcl‐2 and Sirt1 (Ding & Lu, ), and was also associated with adipogenesis (He et al, ). These significant differences in expression suggested that these miRNAs, which promote or impede cell proliferation, might be related to muscle growth and development between SMB chicken and DH chicken.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-204-5p exerted antitumor activity by suppressing melanoma cell invasion [ 29 ]. More importantly, miR-204 was found to be decreased in RB, and miR-204 re-expression inhibited RB cell tumorigenesis and progression [ 2 , 30 ]. In this study, we confirmed miR-204-5p was a target of LINC00202, and miR-204-5p expression was negatively regulated by LINC00202 in RB cells.…”
Section: Discussionmentioning
confidence: 99%
“…Retinoblastoma (RB) is an aggressive intraocular malignancy of infant and childhood, around accounting for 2.5–4% of all pediatric malignancies [ 1 ]. Early and effective treatment can preserve part of the visual function and achieve a longer survival time in children with RB; however, the optimal treatment time will be delayed if there is no timely diagnosis and treatment, thus resulting in a poor prognosis in children with RB [ 2 , 3 ]. Therefore, pinpointing the fundamental mechanism in the occurrence and development of RB and finding new targets to improve the treatment and prognosis of RB are necessary.…”
Section: Introductionmentioning
confidence: 99%